AKTIVITAS KOMUNIKASI PEMASARAN PT ARAH DUNIA TELEVISI PADA PROGRAM RAMADHANKU DI JOGJA - Tasya Yuni Azzahra; Berlian Primadani Satria Putri (Metacommunication: Journal of Communication Studies, 2023)
In the current digital era, new media, such as social media, have emerged abundantly. These new media platforms serve similar functions to television, providing information and entertainment, and can be seen as potential substitutes for television due to their accessibility and availability anywhere. To remain relevant in this evolving era, television networks have adapted to the trends by shifting towards digital television that can be accessed through gadgets. ADITV is one of the local Islamic television stations in Yogyakarta that has made this transition to digital television. One of ADITV's programs that reflects its Islamic identity is "Ramadhanku di Jogja." Marketing communication activities need to be conducted to sustain its position amidst the emergence of new media. Therefore, this research aimed to explore the marketing communication activities of PT Arah Dunia Televisi in the program "Ramadhanku di Jogja" using the concepts of marketing communication (Kotler & Keller, 2012) and marketing communication mix (Firmansyah, 2020). The research methodology employed is qualitative descriptive, involving data collection through interviews, observations, documentation, and literature review, utilizing source triangulation and technique triangulation as data validity techniques. The findings of this study indicate that ADITV has implemented marketing communication activities in the program "Ramadhanku di Jogja," including advertising, sales promotion, public relations and publicity, personal selling, and direct marketing, with a stronger focus on conventional marketing approaches such as personal selling and direct marketing.